Transaksi Online Nasabah Kartu Kredit Pada Consumer Loan Center PT. Bank Negara Indonesia (Persero) Tbk Cabang Denpasar - I Gusti Ayu Diah Pramesti Dewi; Anak Agung Ayu Ngurah Sri Rahayu Gorda (Cakrawala Repositori IMWI, 2023)
This study aims to determine how the bank's responsibility for credit card customers who experience losses in online transactions at the Consumer Loan Center of PT Bank Negara Indonesia (Persero) Tbk Denpasar Branch and efforts to resolve credit card customer losses in online transactions at the Consumer Loan Center of PT Bank Negara Indonesia (Persero) Tbk Denpasar Branch. This research uses empirical research methods that examine data through primary and secondary data analysis. The results of this study indicate that the responsibility of the Consumer Loan Center of PT Bank Negara Indonesia (Persero) Tbk Denpasar Branch is to provide compensation if the results of the investigation prove that the loss was caused by the fault of Bank Negara Indonesia. Efforts to resolve credit card customer losses in online transactions at the Consumer Loan Center PT. Bank Negara Indonesia (Persero) Tbk Denpasar Branch were resolved through internal settlement by Bank Negara Indonesia, namely by submitting an apology statement and providing compensation to credit card customers.